Endodontic treatment complexity and associated factors - Lilian Toledo Reyes; Mireily Alfonso Carrazana (Editorial Ciencias Médicas, 2016)
Introduction: classifying the complexity of endodontic therapy makes it possible to identify factors which may interfere with its success. Objective: determine the correspondence between the duration of root canal treatment and the complexity assigned to it on the Endodontic Case Difficulty Assessment Form. Methods: a prospective longitudinal descriptive study was conducted based on two-staged cluster sampling. The resulting study group was composed of 82 patients. A form was used which lists the factors associated with the complexity of endodontic treatment, collected through interviews and clinical and radiographic examination. Data were processed with the statistical software SPSS version 15.0. Use was made of descriptive statistics techniques (absolute frequencies and percentages). The variables studied were age, sex, pathological antecedents, anesthetics, patient behavior, mouth opening, gagging, complications, radiographic difficulty, diagnosis, position in the arch, dental inclination and rotation, crown morphology, root apex, alteration in the number of roots, bifurcation, duct visibility and size, chamber access, presence of calcifications, resorption, periodontal disease and complexity of the treatment. Results: in 80.8 % of the patients, the category of high treatment difficulty had a duration of 6 to 10 weeks. Moderate or intense pain and extended swelling were present in 29.3 % of the cases. The following factors related to the diagnosis and treatment were observed: extensive restorations, moderate difficulty to obtain and interpret the radiographic image, moderate dental inclination and visible ducts, occurring in 23.2 %, 22.0 %, 20.7 % and 19.5 % of the cases, respectively. Conclusions: treatment duration increases in keeping with the complexity assigned by the form. It is important to evaluate the factors associated with treatment difficulty to foster a more reasonable approach to each specific situation.